Gender roles and constraints in enhancing hybrid chicken production for food security in lower Eastern Kenya. - John K Musyoka; Wilckyster N Nyarindo; Robyn Alders; Hezron N Isaboke (PLoS ONE)
The adoption of hybrid chicken production as a source of income and food security among smallholder farmers has recently taken significant global attention. However, the effect of adoption of hybrid chicken across different genders on household food expenditure and food security remains unknown. This study employed propensity score matching (PSM) and endogenous switching regression (ESR) models to analyze the effect of adoption of hybrid chicken on smallholder households' consumption expenditure and food security in Machakos County. The PSM and ESR models were estimated on a sample of 582 households selected using multistage stratified random sampling method. The descriptive results indicated that adopters of hybrid chicken spent on average KES 1296 compared to the non-adopters who spent KES 1400 on food consumption per month. Furthermore, the adopters of hybrid chicken were more food secure compared to the non-adopters. About 74% of female were also likely to experience chronic food insecurity compared to their male counterparts. The econometric results indicated that farm location, access to credit, access to market, access to feeds, group membership and cost of feeds significantly influenced the adoption of the hybrid chicken production for both male and female decision makers. The average treatment effect results showed that non-adopters spent higher costs on food consumption. Moreover, half of the adopters of hybrid chicken were food secure compared to the non-adopters. The treatment effects of adopting hybrid chicken on household food consumption and food security were positive suggesting that adopters benefited more compared to the non-adopters. To boost food security, this study recommends the National and County governments to develop a facilitating policy environment which supports chicken production systems that are socially, environmentally and economically sustainable while enhancing appropriate technical and extension support to enable cost effective chicken production, marketing, and disease control.